Reação de cultivares de soja e utilização de Trichoderma spp. para o manejo integrado de Meloidogyne javanica - Balardin, Ricardo Rubin (2019)
Soybean is considered the most economically important crop in Brazil, but its yield may be reduced due to pathogens and pests, if not controlled. Plant-parasitic nematodes are responsible for part of this decrease. Among the nematodes of the genus Meloidogyne, the Meloidogyne javanica is the most worrying due to its large number of hosts and its wide geographical distribution. To reduce the use of chemical control, to mitigate environmental damage, has been opted for alternative controls. Integrated management is the set of controls in which biological control, genetic control, physical control, and cultural control assist in reducing the use of chemical control, but with the same efficiency. The objective of this work was to evaluate different soybean genotypes regarding their reaction to M. javanica, and to evaluate if isolates of Trichoderma from different regions of Brazil can control M. javanica. The inoculum was obtained from soybean plants and reinoculated in tomato for proliferation. For the reaction test, 37 soybean cultivars were tested, which were inoculated for each plant 5,000 eggs + second stage juveniles (J2), with six replications each, also containing control treatment. The experiment was evaluated 60 days after inoculation, weighing the roots, and counting the number of galls and number of nematodes per gram of root to calculate the reproduction factor. For the in vitro tests of parasitism, and mortality and egg + J2 hatching inhibition, 40 Trichoderma isolates were obtained (4 isolates from the Midwest, 7 isolates from the Southeast and 29 isolates from the South). Next, a suspension of nematodes was made and individually separated 50 eggs + J2 that was passed to individual wells of the Elisa plate, and a spore solution from each isolate was pipetted into each well for parasitism test and a fungal filtrate solution for each isolate for the mortality test and egg + J2 hatching inhibition. After 15 days of application parasitism, 48 hours after application mortality was evaluated and 21 days after application inhibition of egg + J2 hatching was evaluated. All cultivars had reproductive factor greater than 1, which characterizes susceptibility to M. javanica. The in vitro tests resulted in values above 85.50% parasitism, 65.30% mortality of J2 and 66.00% inhibition of egg + J2 hatching. It can be concluded that the use of Trichoderma and less susceptible cultivar, such as FPS ATALANTA with FR = 1.2, can help the management of M. javanica in the field.